Development of gastronomic tourism in the Bakas Klungkung tourism village - Kesuma, I Putu Yoga Jaya; Efendi, Moch Nur; Mahendra, I Wayan Eka (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Bakas Village is located in Klungkung Regency, Bali, Indonesia, and is known as a tourist village. Bakas Village offers visitors an authentic cultural and natural experience. Even though it may not be as big as culinary tourism destinations in larger areas, Bakas Village can provide a unique Balinese gastronomic tourism experience. Gastronomic tourism is a fun way to travel, while experiencing cultural diversity through food. Gastronomic tourism has a unique appeal because it allows tourists to explore new flavors and tastes. The development of gastronomic tourism in Bakas Village, Klungkung Regency, has local culinary potential as the main tourism attraction. This research aims to identify internal and external factors that influence the development of gastronomic tourism in Bakas Village, Klungkung Regency using a qualitative descriptive method through SWOT analysis (strengths, weaknesses, opportunities, threats). The results of this research found that by creating authentic culinary experiences through collaboration with industry players, involving local communities, utilizing digital technology, and partnerships with local educational institutions, Bakas Village can increase the visibility and attractiveness of gastronomic tourism.